2022
DOI: 10.33050/atm.v7i1.1736
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of Service Quality on Company Reputation on Purchase Decisions for Professional Recruitment Services

Abstract: This study aims to analyze the effect of company reputation and service quality on purchasing decisions for headhunter services. This study is to determine the basis for consumer considerations in choosing a headhunter company, and for headhunter companies this research can be a reference in maintaining relationships with their customers. There are 3 hypotheses tested, and this study uses quantitative methods by conducting surveys. The sampling method is using probability sampling with a sample size of 115 res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 12 publications
0
18
0
2
Order By: Relevance
“…The data source for this research is primary data obtained from interviews with informants at the Coordinating Ministry for Economic Affairs of the Republic of Indonesia, especially Deputy IV for digital economy, Pushansiber Ministry of Defense and Ministry of Communication and Information. While the secondary data sources in this study are data obtained from reports and other data that can be used as a reference for Indonesia's economic growth [19] [20].…”
Section: Methodsmentioning
confidence: 99%
“…The data source for this research is primary data obtained from interviews with informants at the Coordinating Ministry for Economic Affairs of the Republic of Indonesia, especially Deputy IV for digital economy, Pushansiber Ministry of Defense and Ministry of Communication and Information. While the secondary data sources in this study are data obtained from reports and other data that can be used as a reference for Indonesia's economic growth [19] [20].…”
Section: Methodsmentioning
confidence: 99%
“…Putra and Isfandayani (2020) found that behavioral control is the most significant effect on waqif to pay cash waqf. The other study found that religious commitment, attitudes, subjective norms, and intention has a positive and significant effect on pay waqf (Fernando et al, 2022). Therefore, this study will explore more about the behavioral intentions of wakif who waqf through CWLS in Indonesia.…”
Section: Introductionmentioning
confidence: 92%
“…It also provides reference for the management, support, and development of minors' service positions in public libraries. Bintoro B P K [7] et al analyzed the impact of company reputation and service quality on headhunting service purchase decisions, and discussed the factors that candidates need to consider when choosing a headhunting company. Rodrigues D [8] et al investigated how different digital marketing tools and strategies affect recruitment effectiveness.…”
Section: Related Literature Reviewmentioning
confidence: 99%